Teleparalelismo: formulação hamiltoniana e estrutura de vínculos - Rezende, D. J [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
In the present work we study some properties of the teleparallel equivalent of general relativity. In the first chapter, we analyse different ways to obtain the teleparallel Lagrangian. In the second, we make an introduction to the dynamics of constrained systems, and in the third we study the ADM formulation of teleparallel gravity, obtaining its constraint algebra. Finally, we make an analysis of the teleparallel equivalent to the Ashtekar variables

No presente trabalho, faremos um estudo de algumas propriedades da versão teleparalela da relatividade geral. No primeiro capítulo, estudaremos diferentes maneiras de obter sua Lagrangiana. No segundo, faremos uma introdução à dinâmica de sistemas vinculados, e no terceiro estudaremos a formulação ADM do teleparalelismo, obtendo a álgebra dos vínculos. Por fim, estudaremos o equivalente às variáveis de Ashtekar teleparalelas
Keywords: Gravitação; Gravitation